2017
DOI: 10.1002/lary.26934
|View full text |Cite
|
Sign up to set email alerts
|

Safety of outpatient thyroidectomy: Review of the American College of Surgeons National Surgical Quality Improvement Program

Abstract: 2c. Laryngoscope, 128:1249-1254, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 21 publications
5
47
0
Order By: Relevance
“…11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications. [9][10][11] Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients. Although there are potential liabilities to discharging patients the same day as their operation, there are also risks associated with longer hospital stays, as may be evidenced by this study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications. [9][10][11] Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients. Although there are potential liabilities to discharging patients the same day as their operation, there are also risks associated with longer hospital stays, as may be evidenced by this study.…”
Section: Discussionsupporting
confidence: 83%
“…Another study at the Fallon Clinic (Worcester, MA) similarly reported low complication rates and modest savings from same‐day parotidectomies . The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications . Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These data compare favorably to the literature on outpatient thyroidectomy, with complication rates of 5% to 12% reported for patients undergoing hemi or total thyroidectomy, and demonstrating that when patients are carefully selected, the majority can be managed on an outpatient basis …”
Section: Discussionsupporting
confidence: 67%
“…Thyroidectomy is a more common procedure than parathyroidectomy, although with similar safety profiles, and several recent publications have determined thyroidectomy to be a safe outpatient procedure. 15,16 McLaughlin et al 15 performed an analysis of 76,604 cases of partial and total thyroidectomy from NSQIP from 2012 to 2014 and identified a 1.4% 30-day readmission rate and 1.9% reoperation rate. Over time, there was a positive trend in the number of outpatient procedures.…”
Section: Discussionmentioning
confidence: 99%